Students’ Perceptions Towards Extensive Reading In Efl Contexts - Rini Lindawati (ITScience (Information Technology and Science), 2021)
Most university students are struggling in learning English as Foreign Language. The utilization of an extensive reading strategy will potentially promote more striking influential impacts on EFL learners’ target language proficiency. The students' perceptions influence the success of teaching and learning English. The research aimed to know the students’ perception of Extensive Reading in EFL contexts. The researcher used the Qualitative Research method. This study was conducted in Universitas Islam Majapahit. The researcher selected twelve senior students of the English language education department who have already received the extensive reading subject in their previous semesters. The researcher collected the data through semi-structured interviews. The data were then analyzed by following Miles and Huberman’s (1994) framework. The results showed that the students had positive perceptions toward Extensive Reading practices. They considered if Extensive Reading is a reading activity for pleasure and information search where they can read material without any restraint. Besides, Extensive Reading also contributed to developing their comprehension and English skills such as listening, speaking, reading, writing, vocabulary mastery, and grammar. Moreover, Extensive Reading enabled them to enjoy the learning experience.